Index Novus Litteraturae Entomologicae. - Groll, Eckhard K. (Contributions to Entomology = Beiträge zur Entomologie, 2012)
The “Index Novus Litteraturae Entomologicae”, a completely revised new edition of the “Index Litteraturae Entomologicae : Serie I : Die Welt-Literatur über die gesamte Entomologie bis inclusive 1863” (Horn & Schenkling 1928-1929) has been published by the Senckenberg Deutsches Entomologisches Institut (SDEI) in Müncheberg. This bibliography of the literature on entomology from the beginning until 1863 is now available in the Internet (http://sdei.senckenberg.de/index) as an online database free of charge. The history of work on the new edition, the scope of the necessary research and the essential features of the database application are presented.KeywordsBibliography, literature on Entomology, online database.